The knife of never letting go - Ness, Patrick 1971- (Chaos walking, 2008)
Pursued by power-hungry Prentiss and mad minister Aaron, young Todd and Viola set out across New World searching for answers about his colony's true past and seeking a way to warn the ship bringing hopeful settlers from Old World.